Utility of dimethylsulfoxide to preserve synovial fluid samples for microcrystal detection and identification - Fernando Pérez-Ruiz; Elsa Lopez-Bardón; Frédéric Lioté; Naomi Schlesinger; Till Uhlig; Juan J. Mateos-Mazón (Exploration of Musculoskeletal Diseases, 2023)
Aims: To study whether the addition of dimethylsulfoxide (DMSO) to synovial fluid (SF) samples could be helpful to store frozen samples to improve the rates of detection and identification of crystals. Methods: Cross-sectional study of samples of SF consecutively obtained. Three aliquots were generated: one for immediate observation by a senior observer, and 2 to be frozen, one with 10% DMSO (DMSO+) and one without DMSO (DMSO–). Each aliquot was randomly allocated and blinded for further observation when once the samples were unfrozen 3 months afterward. Variables included for analysis were total leucocyte count, detection of crystals, identification of present crystals as monosodium urate (MSU) or calcium pyrophosphate (CPP), number of fields to the first crystal observation, and number of crystals per field. The vitality of leucocytes was evaluated using a trypan blue stain. All samples were examined using ordinary light and polarized light with a red compensator, and unfrozen samples by both senior and junior observers. Results: In the 30 reference samples of SF studied, the mean leucocyte count was 13.1 × 109/L, and 18/30 samples showed crystals (8 MSU, 10 CPP). Once unfrozen, leucocyte counts were 58% lower in DMSO aliquots vs. 22% in DMSO+ aliquots, with vitality (> 50% cells) reduced from 100% in the reference sample to 76.6% in the DMSO+ aliquots to none in the DMSO− aliquots. Agreement in the detection of crystals was much better in DMSO+ aliquots than DMSO− (kappa 1.00 vs. 0.69 and 0.65 vs. 0.11 for the senior and junior observers respectively). Moreover, 4/5 false-negative crystal detection in DMSO− aliquots showed CPP in the reference simple, even though a high density of crystals was observed in the reference sample. Conclusions: The addition of 10% DMSO to SF samples allows freezing and storage with a small loss of leucocyte counts and excellent agreement in the detection and identification of crystals. Cellular lysis may account for the false negative results in aliquots without DMSO, especially in the case of CPP, non-refringent crystals.